Influence of spray-dried plasma source on growth performance of weanling pigs - Rantanen, M.M.; Smith, J.W. II; Richert, B.T.; Friesen, K.G.; Russell, L.E.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Six hundred twenty six pigs (initially 9 lb and 13.2 d of age) were used in a 28-d growth trial to determine the effect of spraydried porcine (SDPP), spray-dried bovine (SDBP), and low-ash porcine plasma (LAPP) on growth performance in the early-weaned pig. Pigs were allotted by weight to one of 10 dietary treatments with 8 to 10 pigs per pen and 7 replicate pens per treatment. The control diet was corn-soybean meal-based and contained 14.44% dried skim milk with no plasma added. Each plasma source (2, 4, and 6%) replaced dried skim milk in the control diet. The LAPP is a similar product to SDPP with the ash component removed. Therefore, the protein content is higher, and slightly lower inclusion rates were required at 1.79, 3.59, and 5.38%. Phase I diets were formulated to contain 1.5% lysine, .42% methionine, .9% Ca, and .8% P. SBM was held constant throughout all the diets at 16.31% with 25% dried whey and 4% fish meal added. On d 14 postweaning, all pigs were switched to a common Phase II milo-SBM based diet. Phase II diets were formulated to 1.25% lysine, .35% methionine, .9% Ca, and .8% P; contained 2.5% spray-dried blood meal and 10% dried whey; and were fed in meal form. Adding any of the plasma sources to the diet from d 0 to 7 after weaning resulted in a linear improvement in average daily gain (ADG) and average daily feed intake (ADFl). Pigs fed diets containing plasma also consumed more feed and were more efficient in feed conversion (F/G) compared to pigs fed the control diet. Adding plasma to the diet also improved ADG and ADFI from d 0 to 14 postweaning. No interactions occurred between level and source; however, pigs fed diets containing SDPP or LAPP had slightly higher ADFI than pigs fed diets containing SDBP d 0 to 14. Feeding a common Phase II diet from d 14 to 28 postweaning had no effect on growth performance. Overall, the pigs fed the plasma sources had greater ADG and ADFI than pigs fed the control diet. These data confirm that feeding spray-dried plasma protein improves growth performance from d 0 to 14 postweaning.
Keywords: Swine; Plasma; Growth